Electric double layer and electrokinetic potential of pectic macromolecules in sugar beet - Kuljanin Tatjana A.; Lević Ljubinko B.; Mišljenović Nevena M.; Koprivica Gordana B. (Acta Periodica Technologica, 2008)
Electrokinetic potential is an important property of colloidal particles and, regarding the fact that it is a well defined and easily measurable property, it is considered to be a permanent characteristic of a particular colloidal system. In fact, it is a measure of electrokinetic charge that surrounds the colloidal particle in a solution and is in direct proportion with the mobility of particles in an electric field. Gouy-Chapman-Stern-Graham's model of electric double layer was adopted and it was proven experimentally that the addition of Cu++ ions to sugar beet pectin caused a reduction in the negative electrokinetic potential proportional to the increase of Cu++ concentration. Higher Cu++ concentrations increased the proportion of cation specific adsorption (Cu++ and H+) with regard to electrostatic Coulombic forces. Consequently, there is a shift in the shear plane between the fixed and diffuse layers directed towards the diffuse layer, i.e. towards its compression and decrease in the electrokinetic potential or even charge inversion of pectin macromolecules.